FUNGSI KOMUNIKASI PEMERINTAH DALAM PENERAPAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Febrian, Ranggi Ade (UIR PRESS, 2018)
include (1) providing recognition and respect for existing village with diversity before and after the formation of the Republic of Indonesia; (2) provide clarity and legal certainty on the status of the village in the constitutional system of the Republic of Indonesia for the sake of justice for all Indonesian people; (3) to preserve and promote the customs, traditions, and culture of the village; (4) encouraging initiative, movement, and the participation of the village community and the potential for development of village assets to the common welfare; (5) form a professional Village Government, efisien and effective, open, and accountable; (6) improve public services for the people of the village in order to accelerate the realization the general welfare; (7) increases the resistance of social culture in order to create the village of villagers who are able to maintain social cohesion as part of national security; (8) promote the economy of the village community and overcome the gap of national development; and (9) to strengthen the village community as a subject of development. But the substance of these goals difficult to implement if no optimization performed by the communication functions of government. In this paper the author tries to describe how the optimization of government communications in the application of Law No. 6 of 2014 concerning the village with 3 communication functions by using the theory of Robbins including oversight function, the function of motivation, and functions of information, coupled with the function of empowerment in the concept of government communications.